Spletni dnevniki kot alternativno medijsko sredstvo etničnih skupin/manjšin - Čeru, Julija (Monitor ISH, 2008)
Our purpose is to analyse blogs as an alternative media discourse of ethnic groups/minorities from former Yugoslavia in Slovenia. The crucial question is: Can the communication of ethnic groups/minorities through blogs meet their basic need to be included in the media and society, or can blogs only serve as a storage area for their opinions, problems, and needs? A case study reveals that the use of virtual media holds promise, both with regard to the attested need and to the existing virtual communication.
Keywords: etnične skupine; narodne manjšine; mass media; množični mediji; spletni dnevniki; blogi; communication; komuniciranje; Slovenia; Slovenija